PENGARUH LINGKUNGAN SEKOLAH DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X DI SMA NEGERI 8 KOTA JAMBI - Kasiono, Fitri Yansah, (SJEE (Scientific Journals of Economic Education), 2018)
This study aims to determine the description of respondents and the influence of school environment and learning discipline on student learning outcomes on the subjects of economy class X in SMA Negeri 8 Kota Jambi. Based on data analysis on the results of research that there is a significant influence between school environment and learning discipline on student learning outcomes on the subjects of economy class X in SMA Negeri 8 Kota Jambi. With result of model summary R = 0,415 and R Square = 0,210. In ANOVA, the value of F = 6.019 with α (sig) = 0.001. Because α (Sig) <0.05, then regression can be used to predict school environment and discipline learning at 95% confidence level. Based on the value of B constant for X, we can make a regression equation that is Y = a + X1 + X2 = 71,388 + 0,321 + 0,111. And, for t arithmetic X1 = 4.196, and t arithmetic X2 = 5.139 then t arithmetic> t table. This means that t count> t table. That is, the results of this t test indicate that the school environment (X1) and learning discipline (X2) have a positive and significant influence on the learning outcomes (Y) students of the class X economic subjects in SMA Negeri 8 Kota Jambi. Keyword : School Environment, Learning Discipline, Learning Outcomes.